GRAVITY EVIDENCE ON THE THUAN HAI-MINH HAI FAULT AND FAULTS SYSTEM IN SOUTH AND SOUTH -CENTRAL VIETNAM CONTINENTAL SHELF - Dung, Tran Tuan (Vietnam Journal of Marine Science and Technology, 2014)
The South and South-central Vietnam continental shelf is a region with the diversely complicated conditions of geology. In spite of over the past many years of investigation, the fault systems in many places have remained poorly understood. In this paper, the author has studied and applied some techniques for interpretation of the newest gravity data and others, which are frequency filtering, gravity horizontal gradient and maximum horizontal gradient, in order to determine plainly the main faults systems in the South and South-central Vietnam continental shelf and also clear up whether or not as well as the location of the fault named ‘Thuan Hai - Minh Hai'.